TOTAL EVENTS OF HEART FAILURE WITH PRESERVED EJECTION FRACTION IN PATIENTS WITH TYPE 2 DIABETES TREATED IN INTERNAL MEDICINE CLINICS AROUND BOGOR, INDONESIA: BUITENZORG DIABETES STUDY - Sibarani, Roy Panusunan; Taradika, Mahisa (Journal of the ASEAN Federation of Endocrine Societies, 2022)
INTRODUCTION Type 2 diabetes (T2D) increases the risk of developing heart failure (HF) symptoms and HF hospitalisation. In Indonesia, ADHERE Study of HF found 31.2% had T2D and this led the patients to readmission and mortality. The high prevalence of diabetes in HFpEF identifies a systemic pro-inflammatory state induced by comorbidities as the cause of myocardial structural and functional alterations. We have no data of the occurrence of HFpEF in people with T2D in Indonesia and this study intended to provide data of T2D patients with HFpEF as an insight for a comprehensive management of diabetes and heart disease. METHODOLOGY This study is a multi-center cross-sectional, observational study of 153 patients with T2D. We used medical records to collect data on duration of diabetes, age, BMI, glycated hemoglobin, renal function, albuminuria and echocardiography. We observed the symptoms of heart failure, anti-hypertensive medications and oral glucose lowering drugs used. RESULTS Out of 153 subjects with echo, 65% showed HFpEF. The patients with no symptoms but have a diastolic dysfunction and normal EF were evidently in the older group, mostly overweight or obese. 79% had glycated hemoglobin below 9%. In patients with duration of diabetes > 8 years, 36% were found to have HFpEF, among patients with duration of diabetes < 8 years with proteinuria, 43% have HfpEF. CONCLUSION HFpEF is often found among patients with type 2 diabetes in Bogor Indonesia mostly with diabetes duration of more than 8 years and with proteinuria.